ANALISIS PERFORMA POMPA 1-P-03A PADA UNIT CRUDE DISTLATION - Samuel Andytyaman Nernere; Yusnita La Goa (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to analyze the performance of the 1-P-03A centrifugal pump in the Crude Distillation Unit (CDU) of PT Kilang Pertamina Internasional RU VII Kasim and compare the actual operational data of the pump with its design data. The data collection method was carried out from the control room on June 7-11, 2023, including parameters of rotational speed (rpm), flow rate, suction pressure, discharge pressure, head, shaft power (BHP), hydraulic power (WHP), and efficiency. The actual data was compared with the pump design data. The performance calculation uses the formula of total pressure, pump head, WHP, BHP, and efficiency. The results of the analysis show the average actual data: rotational speed 2432 rpm, discharge 208 m³/hour, head 93.75 m, BHP 38 kW, WHP 75 kW, and efficiency 50%. The highest discharge value reached 244 m³/hour with an efficiency of 54%, while the lowest was 185 m³/hour with an efficiency of 48%. All actual data is below the design data (design rotational speed 2958 rpm, design flow rate 432 m³/hour, design head 139.5 m). The graph shows a linear relationship between flow rate and shaft power and hydraulic power, and efficiency is directly proportional to flow rate. The performance of pump 1-P-03A is still below design capacity, allegedly due to the condition of the plant which will undergo Turn Around (annual repair) so that the operation is less than optimal. The pump is still operational but requires periodic evaluation to achieve optimal efficiency at the Best Efficiency Point (BEP).